Kinetic Analysis of Oleic Acid Esterification Using Lipase as Catalyst in a Microaqueous Environment - Mohd Sabri, Mahmud; Safinski, Tomasz; Nelson, Mark I.; Sidhu, Harvinder S.; Adesina, Adesoji Adediran (American Chemical Society, 2010)
This paper reports the lipase-catalyzed esterification of oleic acid (with ethanol) in a batch reactor at temperatures between 298 and 338 K using a wide range of the reactant ratio, β (0 < β < 2). All kinetic runs were performed under conditions of negligible transport limitations. The sigmoidal behavior evidenced from the initial rate−substrate concentration curve suggests the allosteric nature of the acrylic-supported Aspergillus lipase, and hence, the data were described by a non-Michaelis Menten kinetic model. The associated oleic acid binding coefficient and ethanol inhibition constant were obtained as 2.382 and 1.643 mmol L−1, respectively. The allosteric effect was attributed to conformational change in the enzyme site occasioned by the presence of trace amounts of water formed within the first few minutes of the reaction. Indeed, the transient water concentration profile at different β values revealed an initial overshoot in water concentration before the relaxation to final equilibrium value after about 6 h. The appearance of the initial overshoot increased with decreasing β. The water concentration history is symptomatic of two first-order interacting processes fed by a self-propagating input consistent with the two-enzyme state concerted symmetry proposition for nonlinear feedback autoregulatory behavior. The rate-temperature envelope showed a maximum at about 318 K, suggesting protein denaturation above this temperature. Even so, a fit of the rate data obtained between 298 to 318 K gave an activation energy of 22.4 kJ mol−1, typical of many enzymatic reactions. FTIR spectra of the catalysts displayed peaks at 1723.23 and 1666.12 cm−1 assigned to COO− and NH2+ groups, respectively, for both fresh and used specimens. BET measurements, however, revealed a significant drop in surface area between fresh (165 m2 g−1) and used (5−20 m2 g−1) catalysts. This was attributed to pore blockage of the immobilized enzyme by the relatively large oleic−acyl−lipase complex left after the reaction.